Improving African American confidence in law enforcement: Recruit to optimize procedural justice, not racial quotas - MacLean, Charles E. (International journal of police science & management, 2021)
Although a common maxim among many practitioners argues that police departments should recruit their way out of the African American confidence race gap by hiring more minority officers, that maxim is unfounded and redirects our recruitment efforts away from hiring to ensure procedural justice and police effectiveness—the two most powerful determinants of African American confidence in the police. The author’s nationwide survey revealed that African Americans living in cities with more racially representative law enforcement agencies were no more confident in local law enforcement than those living in cities where African Americans were underrepresented. That same survey proved, instead, that African American confidence is far higher where local police forces deliver procedural justice and effective policing than where local police forces are merely racially representative. This article presents the survey findings and explores the policy implications for law enforcement recruitment.